O PRINCÍPIO DA CONGRUÊNCIA NA REPERCUSSÃO GERAL DO RECURSO EXTRAORDINÁRIO: UMA ANÁLISE DO TEMA 990 DO STF - GONDIM, LUCAS CAVALCANTE (2021)
The general repercussion, brought up in Brazil by the Constitutional Amendment no. 45, unchained the prevalence of objective features at the extraordinary appeal. That so-called “objectivation” put conventional principles of civil procedural legislation in perspective, since Brazilian Federal Supreme Court downplays dispute resolution in order to emphasize the creation of binding and generalized precedents. Among those, there is the non ultra petita principle, also known as principle of party disposition, whereby the judge should decide only what the petitioners claimed, in a performance of judicial self-restraint. In the abstract judicial review, the congruity principle had already been downplayed at the utmost. Otherwise, in the concrete judicial review – consisted mainly of the extraordinary appeals – the Federal Supreme Court still enforce, with restraints, the non ultra petita principle: the Court is now limited by the contents of its own admissibility appraisal, when the limits of the judgement are defined, and no longer by the litigants claims. However, in the judgement of the theme-case no. 990, the Federal Supreme Court put those criteria away. Despite the opposing motion raised by the General Attorney, the grounds of the case were unilaterally enlarged, undermining general repercussion goals to avoid casuistic approaches in judgments that are to become binding precedents.